Impacto do desmatamento sobre a incidência de doenças na Amazônia - Nilo Luiz Saccaro; Lucas Ferreira Mation; Patrícia Alessandra Morita Sakowski (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– The lack of knowledge about the effects of deforestation on human health is an important gap for management of the environment and health in Brazil and worldwide. In order to assess its occurrence and magnitude, we performed a panel analysis, linking data on deforestation and reportable diseases, by municipality and year, covering 773 municipalities in the Amazon between 2004 and 2012. Estimates were conducted separately for each disease, with the inclusion of controls for fixed effects of municipality, socioeconomic features and provision of public health services. Among the diseases that had sufficient data for analysis, we found that deforestation has a significant effect on leishmaniasis and malaria: annual increases in the municipal deforested area lead to significant increases on incidence. On the other hand, statistically significant effects were not detected for diseases indicated as strong candidates by some authors. The results confirm the existence of health-related deforestation costs, although these do not apply to a wide range of diseases. We highlight the existence of deforestation costs related to health in the Amazon, which must be taken into account both in the management of public health and in making decisions regarding natural capital.
Keywords: Q51; 330; deforestation; Amazon; diseases; public health